2011
DOI: 10.1007/s00380-010-0098-9
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of atherosclerosis between different topographic sites is highly dependent on the type of hyperlipidemia

Abstract: There is a surprising paucity of studies that provide quantitative correlative data on the extent of atherosclerosis between different topographic sites. The impact of cardiovascular risk factors is dependent on the vascular bed, which underlies site-selective effects on progression of atherosclerosis. Therefore, the intraindividual correlation of atherosclerosis between different topographic sites may be dependent on the specific cardiovascular risk profile. The focused objective of the current study is to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Moreover, LDL, VLDL and IDL contain high amounts of cholesterol. Van Craeyveld et al [17] also reported that the relative atherogenicity of VLDL and LDL is dependent on the topographic site, and correlation of the extent of atherosclerosis between different sites is dependent on the type of hyperlipidemia [18]. It may be due to that oxidative stress is different in atherosclerosis-predisposed regions, and atherosclerosis is an inflammatory disease in which various cytokines play a significant role in the progression of vascular lesions [19].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, LDL, VLDL and IDL contain high amounts of cholesterol. Van Craeyveld et al [17] also reported that the relative atherogenicity of VLDL and LDL is dependent on the topographic site, and correlation of the extent of atherosclerosis between different sites is dependent on the type of hyperlipidemia [18]. It may be due to that oxidative stress is different in atherosclerosis-predisposed regions, and atherosclerosis is an inflammatory disease in which various cytokines play a significant role in the progression of vascular lesions [19].…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of variably participating agonists contrast with the intimal emergence of incremental hypoxia/ischemia in terms of increasing matrix proteoglycan deposition and cellular proliferation of smooth muscle cells in particular. Atherosclerosis affecting different topographic sites correlate with the type of hyperlipidemia (Van Craeyveld et al, 2011). The platelet/coagulation systems are incremental sequence events as trophic influence in staged convergence of multiple agonists in intimal injury.…”
Section: Intimal Remodelingmentioning
confidence: 99%
“…In contrast, type IIa hyperlipidemia in patients with familial hypercholesterolemia characterized by increased levels of low-density lipoprotein (LDL) cholesterol specifically induces atherosclerotic plaque deposition in the coronary arteries and proximal aorta and does not lead to atherosclerosis in other vascular beds when unescorted by additional cardiovascular risk factors [ 13 ]. The relative atherogenicity of VLDL and LDL has been demonstrated to differ substantially in different parts of the rabbit aorta in a direct comparison of two rabbit models with matched total cholesterol levels but distinct amounts of VLDL cholesterol and LDL cholesterol [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%